A giant renal angiomyolipoma: a rare case report and review of literature - Bakhshi, Girish D.; Venkateswaran, Rajalakshmi; Dutt, Aishwarya Sunil; Baligar, Sushrut; Jha, Madhu (International Surgery Journal, 2021)
Renal angiomyolipomas (AMLs) are the most common benign tumours of the kidney that occur sporadically in 80% of the patients and are seen associated with genetic conditions such as tuberous sclerosis in rest of the patients. The diagnosis of renal AML pre-operatively have been made easier with the advent of good imaging modalities. The management of these tumours depends on factors such as size, clinical presentation, extent of parenchymal involvement and ranges from a wait and watch strategy to a radical nephrectomy. Herewith, we reported of a giant renal AML who presented with complaints of lump in abdomen with headache and palpitations. She was diagnosed to have a giant renal AML on imaging. The patient was managed with radical nephrectomy after renal AML. A brief case report with review literature was presented here.